Prognostic Value of Biomarkers in Children and Adolescents With Orthostatic Intolerance - Yan, Huijuan; Wang, Shuo; Cai, Hong; Zhang, Juan; Liu, Ping; Wang, Yuwen; Zou, Runmei; Wang, Cheng (Frontiers in Pediatrics, 2021)
Orthostatic intolerance (OI) refers to a series of symptoms that occur during upright standing, which can be relieved when returned to supine position. OI is a common cause of syncope in children and adolescents. In recent years, more and more studies have been carried out to assess the prognosis of OI by using biomarkers, among which flow-mediated vasodilation, left ventricular ejection fraction and fractional shortening, hemodynamic change during head-up tilt test, detection of 24-hour urinary sodium excretion, body mass index, midregional pro-adrenomedullin, and erythrocytic H2S producing rate are relatively stable, inexpensive and easy to obtain. With the help of biomarkers, individualized treatment can be carried out to improve the long-term prognosis of children and adolescents with OI. This article reviews the prognostic value of biomarkers in children and adolescents with OI.